Variability of the IS revealed ionization enhancement by bile acid in mouse plasma. (October 2013) - Olsson, Anders O; Jelvestam, Maria; Ahnoff, Martin
Background: Elevated IS response was observed in 22 out of 157 mouse plasma samples in a 3-month toxicity study. This initiated a root cause investigation.Results: Mass spectra revealed that taurocholic acid (TCA) was present in the samples, partially eluted overlapping the analyte peak. An enhanced IS response (>twofold) was reproduced by injecting TCA together with the IS. Tests with five other drug compounds showed compound dependent matrix effects on ESI; enhancement as well as suppression. The matrix effects did not affect the integrity of study results, most likely due to the use of a 13 C-labeled IS.Conclusion: The variability of TCA levels in plasma as well as the observed instability of the chromatographic retention complicates the evaluation of TCA-induced matrix effects during method development. Thus, monitoring the IS response in incurred samples is a useful tool to evaluate the performance of a validated method.